Exploring the knowledge and attitudes of educational stakeholders and how this influences inclusive education practices in elementary schools: a case study of a rural community in Kasungu, Malawi - Banda, Priscilla (Division of Disability Studies, 2024)
This research study explored knowledge, attitudes, and practices among educational stakeholders in a rural community within Kasungu, Malawi, focusing on inclusive education in elementary schools. A key underlying concern is the pervasive exclusion of children with disabilities from educational opportunities. One of the proposed responses to address this concern is the implementation of inclusive education (IE), which advocates for the full participation and meaningful engagement of all students, regardless of their abilities or differences. However, the successful implementation of IE hinges upon the collaborative efforts and active involvement of various stakeholders, including educators, parents, policymakers, community leaders, and support personnel. Without the collective commitment and engagement of these stakeholders, the effective realization of inclusive education goals remains elusive. Recognizing the imperative to address these challenges, this study sought to investigate the knowledge, and attitudes of education stakeholders in-order to understand how these factors impact the practical implementation of inclusive education in elementary school community in Kasungu Malawi. Following the Knowledge, Attitudes, and Practices (KAP) model, this study employed a qualitative research approach and a descriptive case study design. Data were collected through in-depth interviews and focus group discussions with ten education stakeholders from this community. Participant selection criteria were based on inclusion and exclusion criteria. The data was analyzed thematically and the study revealed diverse perspectives and challenges. Knowledge disparities emerged, as stakeholders understood inclusive education differently, ranging from broader societal transformation to a narrower focus on integrating children with disabilities into mainstream classrooms. Many stakeholders lacked awareness of the National Strategy for Inclusive Education (NSIE), which hindered policy implementation. Attitudes varied among stakeholders, with caregivers and parents supporting the transformative potential of Inclusive Education, while educators and school principals expressed reservations due to readiness and practical constraints, often influenced by the severity of disabilities. Highlighting the critical need for improved collaboration, communication, and community involvement, the study revealed limited collaboration between teachers, parents, and specialists. Low levels of parental and community engagement were linked to factors such as education levels, poverty, and negative attitudes. Knowledge gaps in early identification and support of learners with special needs underscored the need for comprehensive training programs and community engagement initiatives. These findings have significant implications for advancing inclusive education in this study area and similar context. Addressing knowledge disparities and fostering a deeper understanding of inclusive education principles are crucial. This requires comprehensive awareness campaigns and community engagement initiatives to reshape societal attitudes and promote inclusive values. Enhancing professional development for educators through continuous in-service training is essential to bridge the knowledge-attitude-practice gap. Improving collaboration and communication among stakeholders, especially between teachers, parents, and specialists, is key. Encouraging parent-teacher associations and organizing regular meetings to discuss students' progress and challenges can strengthen parental involvement. Adopting a community-based approach, including outreach programs and initiatives, can overcome barriers to parental participation and enhance community engagement. These recommendations provide a valuable guide for advancing inclusive education not only in this Elementary school community in Malawi but also in similar communities worldwide.